Quantitative immunodetection of metalloprotein II in Perinereis aibuhitensis after heavy metal exposure. (November 2020) - Zhao, Huan; Wang, Mengting; Pang, Min; Sun, Jia; Huang, Yi; Gao, Fan; Yang, Dazuo; Zhou, Yibing; Wang, Bin
Abstract: The metal detoxification mechanism is essential for the accumulation activity of some polychaetes. In order to investigate the detoxification function of metalloprotein II in polychaete Perinereis aibuhitensis, a recombinant fusion protein of MP II was successfully expressed in vitro and an anti-MP II polyclonal antibody was got. The tissue distribution of MP II in P . aibuhitensis and the protein expression under Cd, Pb and Zn exposure were detected by ELISA with this antibody. The results showed that MP II was higher in the intestine of P . aibuhitensis, followed by the body wall and parapodium. Cd, Zn and Pb exposure can induced MP II expression, but the change trend of MP II under various heavy metal exposure was different. The amount of MP II induced in P . aibuhitensis increased with the rises of Cd concentration, but there is no significant relationship between Zn and Pb concentration and MP II level. Highlights: A polyclonal antibody specific to P . aibuhitensis MP II is developed for monitoring the heavy metal. The intestine of P . aibuhitensis is the target organ with highest expression of MP II. The toxicity of Cd to P . aibuhitensis is greater than that of Pb and Zn.